Transcatheter Arterial Embolization Treatment for Bleeding Visceral Artery Pseudoaneurysms in Patients with Pancreatitis or following Pancreatic Surgery - Numoto, Isao (Cancers (Basel), 2020)
SIMPLE SUMMARY: Transcatheter arterial embolization (TAE) with coils is widely used to treat pseudoaneurysms; recently, the use of N-butyl cyanoacrylate (NBCA) in TAE has been reported as a feasible and effective approach. The purpose of our retrospective study was to evaluate the efficacy and safety of TAE with coils and NBCA for pseudoaneurysms associated with pancreatitis or pancreatic surgery. This retrospective study included 42 consecutive patients. The technical and clinical success rates, incidence of recurrent bleeding, complications, including pancreatitis, and overall survival after TAE were evaluated. All cases obtained hemostasis after TAE (the technical success rate was 100%). Complications were seen in only two patients. Clinical success rate that was evaluated in terms of 30-day mortality was 76.2%. TAE is then an effective treatment modality for pseudoaneurysms associated with pancreatitis or pancreatic surgery. Accurate diagnosis using angiography contributes to the proper choice of embolic agents and management of such hemorrhages. ABSTRACT: Purpose: To evaluate the efficacy and safety of transcatheter arterial embolization (TAE) for pseudoaneurysms occurring secondary to pancreatitis or because of leakage of pancreatic juice after pancreatectomy. Materials and Methods: This retrospective study included 42 consecutive patients (38 males and 4 females; mean age, 60 years; range, 33–80 years) who underwent TAE for bleeding visceral artery pseudoaneurysms between March 2004 and December 2018. The technical and clinical success rates, incidence of recurrent bleeding, complications, including pancreatitis, and overall survival after TAE were evaluated. Results: Of the 42 enrolled patients, 23 had bleeding due to a complication of pancreatectomy and 19 had bleeding as a complication of pancreatitis. TAE with N-butyl cyanoacrylate (NBCA) or NBCA plus microcoils recurrent bleeding or inability to control bleeding was 15.8% (3 of 19) following TAE with NBCA and 17.4% (4 of 23) following TAE with coils. No clinically significant ischemic events of the pancreas or duodenum were observed in the embolized areas. Serum amylase did not increase compared with the initial levels after any of the procedures. At 30 days after TAE, 32 patients were alive. Conclusion: TAE has a high success rate for the management of hemorrhage, with few complications. The procedure appears to be safe and effective for pseudoaneurysms associated with either pancreatitis or pancreatectomy.